A nationwide indicator to smooth and normalize heterogeneous SARS-CoV-2 RNA data in wastewater. (January 2022) - Cluzel, Nicolas; Courbariaux, Marie; Wang, Siyun; Moulin, Laurent; Wurtzer, Sébastien; Bertrand, Isabelle; Laurent, Karine; Monfort, Patrick; Gantzer, Christophe; Guyader, Soizick Le; Boni, Mickaël; Mouchel, Jean-Marie; et al.
Graphical abstract: Highlights: A wastewater indicator has been designed and tested over the course of a large scale project. It is based on a smoothing technique reducing measurement noise by 19%. It takes into account the differences between laboratory quantification methods. It also accounts for dilution effects such as precipitation. Its good correlation with the incidence rate could make it a credible alternative to mass testing. Abstract: Since many infected people experience no or few symptoms, the SARS-CoV-2 epidemic is frequently monitored through massive virus testing of the population, an approach that may be biased and may be difficult to sustain in low-income countries. Since SARS-CoV-2 RNA can be detected in stool samples, quantifying SARS-CoV-2 genome by RT-qPCR in wastewater treatment plants (WWTPs) has been carried out as a complementary tool to monitor virus circulation among human populations. However, measuring SARS-CoV-2 viral load in WWTPs can be affected by many experimental and environmental factors. To circumvent these limits, we propose here a novel indicator, the wastewater indicator (WWI), that partly reduces and corrects the noise associated with the SARS-CoV-2 genome quantification in wastewater (average noise reduction of 19%). All data processing results in an average correlation gain of 18% with the incidence rate. The WWI can take into account the censorship linked to the limit of quantification (LOQ), allows the automatic detection of outliers to be integrated into the smoothing algorithm, estimates the average measurement error committed on the samples and proposes a solution for inter-laboratory normalization in the absence of inter-laboratory assays (ILA). This method has been successfully applied in the context of Obépine, a French national network that has been quantifying SARS-CoV-2 genome in a representative sample of French WWTPs since March 5th 2020. By August 26th, 2021, 168 WWTPs were monitored in the French metropolitan and overseas territories of France. We detail the process of elaboration of this indicator, show that it is strongly correlated to the incidence rate and that the optimal time lag between these two signals is only a few days, making our indicator an efficient complement to the incidence rate. This alternative approach may be especially important to evaluate SARS-CoV-2 dynamics in human populations when the testing rate is low.